Ghanaian Settlers in Orimedu: Oju Ota, Gender, and Christianity in a Coastal Fishing Community - Adebayo Adewusi (Yoruba Studies Review)
Orimedu was a relatively small coastal community in Ibeju-Lekki area of Lagos State before the area was connected to other parts of state through access roads and electricity in the late 1980s. This article traces the relationship of Orimedu, a predominantly traditionalist and Muslim community, with migrant and Christian fishermen from Ghana and from Togo over the past century or so. It explains that the Ghanaians were welcome despite their Christian identity because they simply adapted to the local religious landscape when they arrived and joined into the worship of Oju Ota, a local deity of fishermen. However, over the past three decades, the Ghanaians have established a Christian community which has been largely accepted.